To protect the soil from irrigation erosion , methods of increasing productivity of the soil and fertileness of winter wheat (International conference on multidisciplinary science, 2024)
According to the lecture of the department of “Food andagriculture” of the UN on the theme “The degradation of soil and water resources,food safety  - developing threat ” 28% of the land that is used nowadays encountered with degradation, and also 8%  is medium and 36% of the used land remained stable and only 10% is considered as improving lands among the lands that is used in the world.